2013
DOI: 10.1111/cge.12219
|View full text |Cite
|
Sign up to set email alerts
|

Split hand/foot malformation with long‐bone deficiency and BHLHA9 duplication: report of 13 new families

Abstract: Split hand/foot malformation (SHFM) with long-bone deficiency (SHFLD, MIM#119100) is a rare condition characterized by SHFM associated with long-bone malformation usually involving the tibia. Previous published data reported several unrelated patients with 17p13.3 duplication and SHFLD. Recently, the minimal critical region had been reduced, suggesting that BHLHA9 copy number gains are associated with this limb defect. Here, we report on 13 new families presenting with ectrodactyly and harboring a BHLHA9 dupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 6 publications
4
24
2
Order By: Relevance
“…Incomplete penetrance was noted, with 19 unaffected obligate duplication carriers. In contrast to one of the previous studies [Klopocki et al, 2012], an increased ratio of affected males to females was not observed, although the manifestations appeared more severe in males [Petit et al, 2013b]. Notably, gain-of-function mutations in BHLHA9 were not identified in other patients in this study who did not have gene duplications.…”
Section: Jcontrasting
confidence: 99%
See 2 more Smart Citations
“…Incomplete penetrance was noted, with 19 unaffected obligate duplication carriers. In contrast to one of the previous studies [Klopocki et al, 2012], an increased ratio of affected males to females was not observed, although the manifestations appeared more severe in males [Petit et al, 2013b]. Notably, gain-of-function mutations in BHLHA9 were not identified in other patients in this study who did not have gene duplications.…”
Section: Jcontrasting
confidence: 99%
“…The tibia was the primary site of long bone involvement in the above two reports of patients with SHFLD associated with 17p13.3 duplications, but involvement of the radii was found in an additional patient [Petit et al, 2013a]. Another study identified BHLHA9 duplications in 13 additional families [Petit et al, 2013b]. Isolated SHFM was present in 57% of affected individuals, while SHFLD was observed in 43%, primarily with unilateral or bilateral tibial involvement, but affecting the radius/arm in two cases and the femur in one.…”
Section: Jmentioning
confidence: 91%
See 1 more Smart Citation
“…Recently, we have identified heterozygous tandem duplications/triplications of an identical 210,050 bp segment harboring BHLHA9 at chromosome band 17p13.3 in 27 of 51 Japanese families with split‐hand/foot malformation (SHFM), SHFM with long bone deficiency (SHFLD) that usually affects the tibia, or the Gollop‐Wolfgang complex (GWC) characterized by femoral bifurcation, tibial hypoplasia/aplasia, and SHFM [Nagata et al, ]. The results provide further support for the involvement of heterozygous copy number gains of BHLHA9 in the development of SHFM and SHFLD [Klopocki et al, ; Petit et al, ], and indicate for the first time the relevance of BHLHA9 overdosage in the occurrence of GWC. Notably, SHFLD and GWC are more frequent in families with triplications than in those with duplications, and the duplications/triplications are found not only in all the 42 affected patients, but also in 22 of 47 clinically normal relatives from the 27 families as well as in 2 of 1,000 Japanese controls [Nagata et al, ].…”
Section: To the Editormentioning
confidence: 63%
“…Recent reports have indicated that 17p13.3 duplications should be considered the commonest cause of SHFM/ SHFLD [714]. In particular, Klopocki et al [9] scrutinized the minimal critical region (11.8 kb) by analyzing 17 families with 17p13.3 duplications, and identified BHLHA9 [which encodes basic helix–loop–helix (bHLH) family member A9] as a novel SHFM/SHFLD-related gene.…”
Section: Introductionmentioning
confidence: 99%